How Corporate Social Responsibility Enhance Banking Sector Customer Loyalty in Digital Environment? An Empirical Study - Muddassar Sarfraz; Muhammad Ibrahim Abdullah; Samina Arif; Jasim Tariq; Ilknur Ozturk (ETIKONOMI, 2022)
This study examines the relationship between corporate social responsibility (CSR) perceptions and customer loyalty in the banking sector while considering the mediating effects of customer satisfaction, corporate image, corporate reputation, service quality between CSR activities and customer loyalty. A self-administered survey was conducted on the banking customers in Pakistan. Based on 221 customers' data, the analysis was performed using the structural equation modeling (SEM) approach. The study results show that CSR positively influences customer loyalty in the banking sector, customer satisfaction, corporate image, and service quality affect the customer-business relationship. Notably, a new finding from the study highlights the importance of the mediating role of corporate image and service quality in enhancing the effect of CSR on customer satisfaction. The research findings provide valuable insights to banks in developing counties on developing a CSR strategy to strengthen customer loyalty.JEL Classification: M19, L21, M10, D22